Disaster monitoring in urban and remote areas using satellite stereo images: A depth estimation approach - Ahmad, R.F. (Institute of Electrical and Electronics Engineers Inc., 2015)
Disaster can occur any time either it is natural or human made. Urban areas are congested and highly populated in big cities. Any kind of natural disaster like earthquake or flood can damage the whole city or partially, depending upon the intensity. To enhance the rescue activities and saving lives; disaster monitoring and management plays a critical role. Many techniques are used these days to monitor and identify the intensity of damage e.g., aerial view of city, SAR, LiDAR, site survey or acquiring the satellite images. Remote sensing to monitor natural disasters has been proven useful for detection of earthquakes, land sliding, flooding, wildfire and volcanic activity. In our paper, we have proposed a method to monitor the disaster using satellite stereo images which can detect and measure the intensity of damage. For preliminary study, we have acquired the satellite images from Quick bird. Depth estimation algorithm on stereo images produces good results to monitor the urban and remote areas infrastructure as compared to the traditional methods like video surveillance. Â© 2015 IEEE.